ANALISIS JENIS FLUIDA RESERVOIR BERDASARKAN NILAI SW DAN LOG SUMUR DS-19, CS-21, RS-23 FORMASI AIR BENAKAT CEKUNGAN SUMATERA SELATAN - Dicky Setiawan Sirait; Rohima Sera Afifah; Karmila Karmila (Sekolah Tinggi Teknologi MIGAS, 2023)
Hydrocarbon exploration currently has a variety of methods in operation to determine and identify a reservoir according to the required parameters. Well log data plays an important role in the development of hydrocarbon exploration. Hydrocarbon saturation can be known by first calculating the water saturation, so the value of Sw is the key to work to determine the type of reservoir and its fluid content at an interval or reservoir zone accompanied by crossover and separation readings on the density & neutron log curve. The research was conducted in the Jambi Sub-basin area, ANONIM field, South Sumatra, DS-19, CS-21, RS-23 wells with shaly sand lithology which produces three productive zones. Based on the results, wells DS-19, CS-21, RS-23 has a gaseous hydrocarbon fluid with Sw value in the DS-19 well of 10.5%, CS-21 well of 27.1%, and RS-23 well of 22.4%.